The effect of transcutaneous electrical nerve stimulation (TENS) and cryotherapy in the relief of pain during labor - Regis, Mariana Meurer; Honório, Gesilani Júlia da Silva; Santos, Keyla Mara dos; Luz, Soraia Cristina Tonon da; Luz, Clarissa Medeiros da; Roza, Thuane da (Manual Therapy, Posturology & Rehabilitation Journal, 2017)
Background: The delivery pain is an unpleasant experience which may generate some insecurity for the woman. Thus, some methods of analgesia need to be studied in order to generate greater comfort for the woman during labor. Objective: to evaluate the effect of transcutaneous electrical nerve stimulation (TENS) and cryotherapy (CRYO) on labor pain. Method/Design: quasi experimental study, randomized sample in two groups: TENS and CRYO. Pregnant women were selected in the Carmela Dutra Maternity (Florianópolis (SC), Brazil) according to inclusion criteria: women which are pregnant for the first time, age (18-40 years) and initial cervical dilatation of 4-5cm. The Visual Analogue Scale (VAS) was used to evaluate pain before and after each intervention. Results: 24 parturient women were studied (TENS = 11, CRYO = 13). In the TENS group, there was a significant result in pain relief after the first application (p = 0.002). VAS was reduced from 8 to 5.5, but not significant. In the CRYO group there was reduction of pain during the first application (p = 0.008), and in the second there was an increase in pain (p = 0.008). There was a significant difference between the techniques in the evaluation performed before the second application, with a lower value attributed to the CRYO group (p = 0.034). Conclusions: CRYO and TENS were effective in relieving pain during the first phase of the initial phase of labor. However, during the treatment, in the parturient women studied, there was maintenance of pain response by the CRYO group and decrease in the TENS group without reduction significant.